2013
DOI: 10.1021/es401019n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Trickery in Soil Organic Matter: Hidden Lignin

Abstract: Binding to minerals is one mechanism crucial toward the accumulation and stabilization of organic matter (OM) in soils. Of the various biochemicals produced by plants, lignin-derived phenols are among the most surface-reactive compounds. However, it is not known to what extent mineral-bound lignin-derived phenols can be analytically assessed by alkaline CuO oxidation. We tested the potential irreversible binding of lignin from three litters (blue oak, foothill pine, annual grasses) to five minerals (ferrihydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 58 publications
7
86
1
1
Order By: Relevance
“…Average weighted carbon-normalized yields in the other six sample types ranged from 1.72 to 2.56 mg 100 mg OC −1 . These values are consistent with previous studies involving plant leachates (Hernes et al, , 2013aPellerin et al, 2010). Carbon-normalized yields in the litters and duffs prior to leaching ranged from 0.72 mg 100 mg OC −1 in the annual grass duff to 6.05 mg 100 mg OC −1 in the annual grass litter, and averaged 3.82 mg 100 mg OC −1 , while post-leaching values were 1.03-6.87 mg 100 mg OC −1 with an average of 4.17 mg 100 mg OC −1 , indicating preferential leaching/degradation of non-lignin plant constituents ( Table 1).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Average weighted carbon-normalized yields in the other six sample types ranged from 1.72 to 2.56 mg 100 mg OC −1 . These values are consistent with previous studies involving plant leachates (Hernes et al, , 2013aPellerin et al, 2010). Carbon-normalized yields in the litters and duffs prior to leaching ranged from 0.72 mg 100 mg OC −1 in the annual grass duff to 6.05 mg 100 mg OC −1 in the annual grass litter, and averaged 3.82 mg 100 mg OC −1 , while post-leaching values were 1.03-6.87 mg 100 mg OC −1 with an average of 4.17 mg 100 mg OC −1 , indicating preferential leaching/degradation of non-lignin plant constituents ( Table 1).…”
Section: Resultssupporting
confidence: 93%
“…Characterizing fractionation effects in lignin biomarkers has significantly improved interpretation of DOM and lignin parameters in various environments, explaining apparent degradation trends that previously were conundrums (Hernes et al, , 2013aSpencer et al, 2008Spencer et al, , 2016. Lignin fractionation studies to date have primarily consisted of snapshot measurements, in which dissolved and particulate lignin is allowed to reach equilibrium, then a single measurement of each is compared to assess the magnitude of fractionation (Hernes et al, , 2013a.…”
Section: Discussion Lignin Relativity As Demonstrated By Fractionatiomentioning
confidence: 99%
“…This is consistent with preferential interactions between Fe oxide minerals and aromatic lignin constituents (Gu et al, 1995;Kaiser, 2003;Riedel et al, 2013). Given that short-range-order Fe oxides are present in most soils (Reyes and Torrent, 1997), Fe-lignin interactions deserve attention as contributors to "hidden lignin" pools that have potentially been obscured due to methodological artifacts associated with common lignin measurements (Hernes et al, 2013). Lignins synthesized with labeled isotopes provide one method to surmount these analytical challenges.…”
mentioning
confidence: 59%
“…In support of the new paradigm, several studies reported that lignin might decompose as fast or faster than bulk SOM (Dignac et al, 2005;Gleixner et al, 1999;Guggenberger et al, 1994;Heim and Schmidt, 2007;Kiem and K€ ogel-Knabner, 2003). Yet, these findings are difficult to reconcile with other studies demonstrating preferential association of aromatic lignin constituents with minerals, especially Fe oxides (Chorover and Amistadi, 2001;Gu et al, 1995;Hernes et al, 2013;Huang et al, 1977;Kaiser, 2003;Riedel et al, 2013). These associations would presumably decrease lignin mineralization, as has been observed for coprecipitates of lignin and ferrihydrite (Eusterhues et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
“…An important contribution to the dissolved organic matter leaching from the litter to the mineral soil is provided by oxidised lignin fragments [63,64]. The nature and role of lignin, especially in mineral soil, is still poorly understood [65,66]. Lignin was a large contributing variable in forest floor leaf litter within our two-block PLS.…”
Section: Discussionmentioning
confidence: 98%